ECONOMIC REHABILITATION IN IRAQ: DIALECTICAL RELATIONSHIP BETWEEN INTERNATIONAL INSTITUTIONS AND REQUIREMENTS OF THE NATIONAL ECONOMY (American Journal of Business Management, Economics and Banking, 2023)
The importance of the research lies in its review of the most important problems of the Iraqi economy since 2004 and the stages through which the economic reform measures have been implemented, as well as how successive governments have dealt with the reform measures laid down by international organizations in Iraq.Although there were potentials, natural resources, and detailed reform programs for the Iraqi economy, they did not continue to advance their economic and financial capabilities, which is the study's problem. Therefore, Iraq needs international organizations to intervene for economic reform and on a continuous basis since the country is constantly exposed to crises, this shows that it has benefited from these programs only in a limited period of time when it has gone through economic and security crises and oil shocks. This shows that it has benefited from these programs only in a limited period of time when it has gone through economic and security crises and oil shocks.